The reality of the size of the public sector and economic growth from the perspective of the Chehy Relationship in Algeria, an econometric study using the ARDL model for the period: (1990-2018) - Amina Bendjeddou; Messaoud Mihoub (Dirassat Journal Economic Issue, 2021)
The study aims to address the relationship between the size of the public sector and economic growth in Algeria for the period between 1990 and 2018, from the viewpoint of Chehy’s relationship, which called for this theory not to exceed 15% in order to avoid the negative and undesirable impact on growth. By relying on econometric methods using the methodology of the ArdL regression model, it was concluded that the incomplete operational level experienced by Algeria, and in light of the need to continue to attract and stimulate the local activity cycles, to the necessity of adopting a maximum rate of 35% to achieve growth rates. Approximately 7%, in both the medium and long term.